Inhibiting autophagy enhances sulforaphane-induced apoptosis via targeting NRF2 in esophageal squamous cell carcinoma - Zhaoming Lu; Yandan Ren; Li Yang; Ang Jia; Yi Hu; Yu Zhao; Wuduo Zhao; Bin Yu; Wen Zhao; Jianying Zhang; Guiqin Hou (Elsevier, 2021)
Sulforaphane (SFN), a natural anti-tumor compound from cruciferous vegetables, has been reported to induce protective autophagy to cancer cells, which might impair the anti-tumor efficiency of SFN. However, the accurate function and mechanism of SFN inducing autophagy in cancers are still obscure, especially in esophageal squamous cell carcinoma (ESCC), one of malignancies with high incidence in North China. Here, we mainly explored the potential function of autophagy upon SFN treatment in ESCC and molecular mechanism. We demonstrated that SFN could inhibit cell proliferation and induce apoptosis by activating caspase pathway. Moreover, we found activation of NRF2 pathway by SFN was responsible for the induction of autophagy and also a disadvantage element to the anti-tumor effects of SFN on ESCC, indicating that SFN might induce protective autophagy in ESCC. We, therefore, investigated effects of autophagy inhibition on sensitivity of ESCC cells to SFN and found that chloroquine (CQ) could neutralize the activation of SFN on NRF2 and enhance the activation of SFN on caspase pathway, thus improved the anti-tumor efficiency of SFN on ESCC in vitro and in vivo. Our study provides a preclinical rationale for development of SFN and its analogs to the future treatment of ESCC.